Financial Ratio Analysis in Predicting Financial Distress at Tourism Companies, Restaurants, and Hotels Listed on the Indonesia Stock Exchange (IDX) 2021 - Sukarno*, Agus; Yacobus, Aryono; Satmoko, Agung (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2023)
This study aims to determine and analyze liquidity, profitability, leverage, and operational cash flow on financial distress in tourism companies, restaurants, and hotels listed on the Indonesia Stock Exchange in 2021. By measuring the effect of liquidity, profitability, leverage, and operational cash flow on financial distress. Financial distress is measured using the X-Score. The method of analysis of this research uses the logistic regression analysis method. The results of this study indicate that liquidity harms financial distress, profitability harms financial distress, leverage has a positive effect on financial distress, and the operational cash flow ratio does not affect financial distress. Keywords: Financial ratios; Financial Distress; Leverage; Oprational Cash Flow X-Score; Profitability Abstrak Penelitian ini bertujuan mengetahui dan menganalisis liquidity, profitability, leverage dan operational cash flow terhadap financial distress pada perusahaan pariwisata, restoran dan hotel yang terdaftar di Bursa Efek Indonesia tahun 2021. Dengan mengukur pengaruh liquidity, profitability, leverage dan operational cash flow terhadap financial distress. Financial distress diukur menggunakan X-Score. Metode analisis penelitian ini menggunakan metode analisis regresi logistik. Hasil penelitian ini menunjukkan bahwa liquidity berpengaruh negatif terhadap financial distress, profitability berpengaruh negatif terhadap financial distress, leverage berpengaruh positif terhadap financial distress, operational cash flow ratio tidak berpengaruh terhadap financial distress. Kata Kunci: Rasio Keuangan; Rasio Arus Kas Operasional; Kesulitan Keuangan; Profitabilitas; Manfaat X-Score